2010
DOI: 10.1002/asia.201000087
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Hydrogen Evolution by [FeFe] Hydrogenase Mimics in Homogeneous Solution

Abstract: To mimic [FeFe] hydrogenases (H(2)ases) in nature, molecular photocatalysts 1 a, 1 b, and 1 c anchoring rhenium(I) complex S to one of the iron cores of [FeFe]-H(2)ases model complex C, have been constructed for H(2) generation by visible light in homogeneous solution. The time-dependence of H(2) evolution and a spectroscopic study demonstrate that the orientation of S and the specific bridge in 1 a, 1 b, and 1 c are important both for the electron-transfer step from the excited S* to the catalytic C, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
72
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(76 citation statements)
references
References 89 publications
2
72
1
Order By: Relevance
“…As compared with those reported in the literature [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] , the durability and activity of the present system are greatly increased; possibly as a result of the stabilization of the components by chitosan confinement leading to consecutive multi-step electron transfer in equilibrium. The importance of the stabilization was also analysed by exchanging chitosan for relatively small and loose aggregates, anionic SDS (0.166 mol l À 1 ) and cationic CTAB (0.055 mol l À 1 , cetyl trimethyl ammonium bromide) micelles 37 .…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…As compared with those reported in the literature [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] , the durability and activity of the present system are greatly increased; possibly as a result of the stabilization of the components by chitosan confinement leading to consecutive multi-step electron transfer in equilibrium. The importance of the stabilization was also analysed by exchanging chitosan for relatively small and loose aggregates, anionic SDS (0.166 mol l À 1 ) and cationic CTAB (0.055 mol l À 1 , cetyl trimethyl ammonium bromide) micelles 37 .…”
Section: Discussionsupporting
confidence: 48%
“…From a photochemical point of view, the electron transfer is triggered by the absorption of a photon by a photosensitizer [13][14][15][16][17][18][19][20][21][22][23][24][25] . Since the first attempt by Sun and Åkermark 34 to construct an artificial photocatalytic system for H 2 evolution in 2003, a large number of synthetic model complexes have been pursued to mimic the structure and functionality of the diiron subunit of the natural [FeFe]-H 2 ase H-cluster [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] . It is encouraging to see that the catalytic efficiency for H 2 evolution from artificial photocatalytic systems using mimics of the diiron subsite of [FeFe]-H 2 ase as catalysts has been increased from null to more than hundreds or thousands of turnover numbers (TON) under different irradiation conditions.…”
mentioning
confidence: 99%
“…Three molecular photocatalysts with a Re I -photosensitizer directly linked to one of the Fe centers of an [Fe 2 S 2 ] unit by linear and rigid bridges in two different linkage orientations were reported by Wu and co-workers. [10] It was found that such ReÀFeFe molecular devices displayed relatively long-lived charge-separated states, formed by oxidative quenching, and they proved to be active for photoinduced H 2 evolution with CH 3 OH as sacrificial electron donor and HOAc as proton source in CH 3 CN/ H 2 O. Although some reports have described electrochemical H 2 production by Ni-or NiFe-based molecular catalysts, [16] photocatalytic H 2 production by Ni complexes has not been described in the literature so far.…”
mentioning
confidence: 97%
“…[5,7,10] It is surprising that a catalyst system comprising an all-carbonyl multinuclear iron complex, [Fe 3 (CO) 12 ], [Ir(bpy)(ppy) 2 ]PF 6 (Hppy = 2-phenylpyridine), and triethylamine (TEA) displayed a high efficiency for visiblelight-driven H 2 production, with turnovers of up to 400 vs. [Fe 3 (CO) 12 ] in THF/H 2 O over 3 h of irradiation, [7] which is the best result ever reported for an Fe-based catalyst system in the photochemical production of H 2 from water reduction. Three molecular photocatalysts with a Re I -photosensitizer directly linked to one of the Fe centers of an [Fe 2 S 2 ] unit by linear and rigid bridges in two different linkage orientations were reported by Wu and co-workers.…”
mentioning
confidence: 98%
See 1 more Smart Citation